(849) Statistical Models for some Economic Phenomena النماذج الإحصائية لبعض الظواهر الاقتصادية - M.W. Mahmoud.; M. V. Radwan. (INP, 2024)
It is of great importance to know the theoretical model that fits a given frequency distribution for any economic pheno- menon. This will help in taking decisions or drawing plans. Two particular economic phenomena are discussed inthis paper :-(i) The distribution of employees according to their wages (ii) The distribution of households according to their percentage of expenditure on food stuffs for rural and urban regions.